2016
DOI: 10.3802/jgo.2016.27.e21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of human papillomavirus genotyping

Abstract: Cervical cancer is the fourth most common cancer in women worldwide, and the human papillomavirus (HPV) is the main causative agent for its development. HPV is a heterogeneous virus, and a persistent infection with a high-risk HPV contributes to the development of cancer. In recent decades, great advances have been made in understanding the molecular biology of HPV, and HPV’s significance in cervical cancer prevention and management has received increased attention. In this review, we discuss the role of HPV g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 71 publications
1
74
0
7
Order By: Relevance
“…Los virus del papiloma humano de alto riesgo (VPH-AR) han sido identificados como agentes causales de cáncer de cuello uterino (Bosch et al, 1995;Walboomers et al, 1999;Zur Hausen, 2002;Schiffman et al, 2016), la detección de VPH-AR aunque es más sensible que la citología para detectar lesiones pre malignas tiene un valor predictivo bajo dado que la mayoría de infecciones son transitorias y solo una fracción pequeña de las mujeres positivas para ADN de virus oncogénicos desarrolla cáncer de cuello uterino (Liaw et al, 2001;Arbyn et al, 2006;Cuzick et al, 2006;Bansal et al, 2008;Choi et al, 2016). Se requiere un test que permita distinguir objetivamente las infecciones transitorias que no van más allá de causar una lesión de bajo grado de las asociadas a transformación oncogénica y mayor riesgo de desarrollar lesiones de alto grado y cáncer cervical.…”
Section: Introductionunclassified
“…Los virus del papiloma humano de alto riesgo (VPH-AR) han sido identificados como agentes causales de cáncer de cuello uterino (Bosch et al, 1995;Walboomers et al, 1999;Zur Hausen, 2002;Schiffman et al, 2016), la detección de VPH-AR aunque es más sensible que la citología para detectar lesiones pre malignas tiene un valor predictivo bajo dado que la mayoría de infecciones son transitorias y solo una fracción pequeña de las mujeres positivas para ADN de virus oncogénicos desarrolla cáncer de cuello uterino (Liaw et al, 2001;Arbyn et al, 2006;Cuzick et al, 2006;Bansal et al, 2008;Choi et al, 2016). Se requiere un test que permita distinguir objetivamente las infecciones transitorias que no van más allá de causar una lesión de bajo grado de las asociadas a transformación oncogénica y mayor riesgo de desarrollar lesiones de alto grado y cáncer cervical.…”
Section: Introductionunclassified
“…It is clear that persistent infection with a high -risk HPV genotype is known to be a major carcinogenic factor, however, various high -risk HPV genotypes have different carcinogenic potentials (8). Therefore, finding out the genotype -specific features of HPV infection would facilitate the expanding of better strategies to prevent and manage cervical cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that human papillomavirus (HPV) infection, in particular HPV16, is relevant in the onset of cervical cancer (2). However, an increasing body of evidence has indicated that the occurrence of cervical cancer is a result of the combined action of multiple factors, since the incidence of HPV infection in women of childbearing age is higher, but the incidence of cervical cancer is lower among these patients (3). Therefore, HPV infection is not the only factor involved in the development of cervical cancer (4,5).…”
Section: Introductionmentioning
confidence: 99%